Triple therapy with deferiprone, idebenone and riboflavin in Friedreich's ataxia – open‐label trial. (14th May 2013) - Arpa, J.; Sanz‐Gallego, I.; Rodríguez‐de‐Rivera, F. J.; Domínguez‐Melcón, F. J.; Prefasi, D.; Oliva‐Navarro, J.; Moreno‐Yangüela, M.
<x xml:space="preserve">Abstract</x> Objectives The objective of the study was to test the efficacy, safety and tolerability of triple therapy with deferiprone, idebenone and riboflavin in Friedreich's ataxia (FRDA) patients in a clinical pilot study. Patients and methods Patients included in this study were 10 males and three females, 14–61 years of age (average 30.2 ± 12.1), diagnosed with FRDA with normal ventricular function. Patients were treated with triple therapy with deferiprone at 5–25 mg/kg/day, idebenone at 10–20 mg/kg/day and riboflavin at 10–15 mg/kg/day for 15–45 months. The efficacy of this triple therapy was assessed by change from baseline on the scale for the assessment and rating of ataxia (SARA) and by the change from baseline in echocardiogram parameters. Results Four patients discontinued due to adverse events (AEs) related with deferiprone. The annual worsening rate (AWR) was estimated in this series as 0.96 (CI 95%: 0.462–1.608) SARA score, whereas AWR for our FRDA cohort was estimated as 2.05 ± 1.23 SARA score. LVMI only decreased by 6.5 g/m2 (6.2%) at the end of the first year of therapy. LVEF remained stable, except in case of three patients. Conclusion Our results seem to indicate some uncertain benefit on the neurological and heart functions of this triple therapy in FRDA.